2023
DOI: 10.3390/jcm12041595
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Bimanual Intensive Functional Training on Somatosensory Hand Function in Children with Unilateral Spastic Cerebral Palsy: An Observational Study

Abstract: (1) Background: Next to motor impairments, children with unilateral spastic cerebral palsy (CP) often experience sensory impairments. Intensive bimanual training is well known for improving motor abilities, though its effect on sensory impairments is less known. (2) Objective: To investigate whether bimanual intensive functional therapy without using enriched sensory materials improves somatosensory hand function. (3) Methods: A total of twenty-four participants with CP (12–17 years of age) received 80–90 h of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…Up until now, improvements in somatosensory function are mostly considered as a potential by-product of motor training [28]. Some studies have indeed shown that after constraint induced movement therapy [29] and bimanual motor therapy [30][31][32] significant improvements in somatosensory function can be detected, although the results are varying depending on the type of participants, specific intervention performed and the outcome measures used. Furthermore, based on the training principle of specificity, it can be expected that interventions designated to specifically address these somatosensory impairments might have a superior effect.…”
Section: Introduction Background and Rationale {6a}mentioning
confidence: 99%
“…Up until now, improvements in somatosensory function are mostly considered as a potential by-product of motor training [28]. Some studies have indeed shown that after constraint induced movement therapy [29] and bimanual motor therapy [30][31][32] significant improvements in somatosensory function can be detected, although the results are varying depending on the type of participants, specific intervention performed and the outcome measures used. Furthermore, based on the training principle of specificity, it can be expected that interventions designated to specifically address these somatosensory impairments might have a superior effect.…”
Section: Introduction Background and Rationale {6a}mentioning
confidence: 99%